2002
DOI: 10.1002/1521-3935(200207)203:10/11<1436::aid-macp1436>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Fast-activated anionic polymerization of -caprolactam in suspension, 1

Abstract: The fast‐activated anionic polymerization of ε‐caprolactam has been performed in suspension in order not only to efficiently dissipate the heat of polymerization, but also to directly synthesize powdered polyamide 6. The continuous phase of the system is composed of polyisobutene oils: five fractions, different in their molecular weights and viscosities, have been used and thoroughly studied in terms of their influence on polymerization yield, as well as on polyamide 6 chemical and physical properties, and on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 8 publications
3
28
0
Order By: Relevance
“…Recently, we reported on the preparation of powdered PA6 using a suspension polymerisation technique 15. The results of our study have clearly shown the applicability of the above method for the preparation of powdered PA6 in one step.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Recently, we reported on the preparation of powdered PA6 using a suspension polymerisation technique 15. The results of our study have clearly shown the applicability of the above method for the preparation of powdered PA6 in one step.…”
Section: Resultssupporting
confidence: 55%
“…[15] The results of our study have clearly shown the applicability of the above method for the preparation of powdered PA6 in one step. However, the problem of particle coalescence does not seem easily solved by this approach and requires the use of specific particle stabilisers.…”
Section: Solution Blendssupporting
confidence: 53%
“…Powdered polyamides with micron-sized particles are of demand in various processing procedures such as flame spraying and electrostatic coating, compression-and rotational molding. [1][2][3][4] In bioengineering, finely divided porous polyamides are an attractive carrier for protein or enzyme immobilization and find applications in solid-phase diagnostics, biosensors, biocatalysts, and bio-separation. [5][6][7] Polymer particles with magnetic or conductive loads are intensively studied in applications requiring stimuli responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is strengthened by the available literature where CI-CLA is synthesized from cyclohexyl isocyanate and CLA at elevated temperatures. [46][47][48] CI-CLA is an electron-deficient carbonyl easing the initial polymerization step comparable to CLA-Ac (Scheme 2, polyamide 6 synthesis). [48] In accordance with this proposal, the solidification times of mixtures containing 3 equivalents of activator (CLA-Ac and Cy-NCO, Table 2, entries 1 and 4) are significantly shorter than for mixtures containing 2 equivalents of activator (Cy-NCO, Table 2, entries 2-3).…”
Section: Doi: 101002/marc202000338mentioning
confidence: 99%